Touching Philosophy, Sounding Religion, Placing Education - Schroeder, Steven (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This book redefines religious studies as a field in which a plurality of disciplines interact. A social science when understood as a body of knowledge, religion is also marked by discovery, appreciation, orientation, and application-an interplay of the arts and sciences. Teaching religious studies involves the question of the occupation of territories and disentangling occupation from violence.